Resenha de: Perspectives on Brazilian History - Castro, Paulo P. de (Revista de História, 1968)
BURNS (E. Bradford) (Editor) . — Perspectives on Brazilian History. Columbia University Press. New York & London, 1967, 235 páfs., US$ 7,50.